THOUGHTS ABOUT THE BIBIKHONIM MOSQUE AND THE HISTORY OF ITS CONSTRUCTION (World Economics and Finance Bulletin, 2023)
This article describes the research, historical written sources and opinions expressed in the works on the Bibikhanum mosque and the history of its construction, which showed the glory and creativity of the great statesman, patron of science and culture during the reign of Amir Temur
Keywords: Amir Temur; Bibikhanim; Samaria; Nizamiddin Shami